Glucose deprivation-induced metabolic oxidative stress and cancer therapy - Simons, Andrean L (2009)
Cancer cells (vs. normal cells) demonstrate evidence of oxidative stress, increased glycolysis, and increased pentose cycle activity. The oxidative stress in cancer cells has been hypothesized to arise from mitochondrial dysfunction leading to increased levels of hydroperoxides, and cancer cells have been proposed to compensate for this defect by increasing glucose metabolism. Glucose metabolism has also been shown to play a role in hydroperoxide detoxification via the formation of pyruvate (from glycolysis) and NADPH (from the pentose cycle). Furthermore, in cancer cells, glucose deprivation as well as treatment with 2-deoxyglucose (2 DG) has been shown to induce oxidative stress and cytotoxicity. Additionally, transformed cells have been shown to be more susceptible to glucose deprivation (and 2DG-)-induced cytotoxicity and oxidative stress than untransformed cells. These results support the hypothesis that cancer cells have a defect in mitochondrial respiration leading to increased steady state levels of O(2)(•)- and H(2)O(2), and glucose metabolism is increased to compensate for this defect. The application of these findings to developing cancer therapies using 2DG combined with inhibitors of hydroperoxide metabolism to induce radio/chemosensitization is discussed, as well as the possibility that FDG-PET imaging may predict tumor responses to these therapies.